2013
DOI: 10.1111/cmi.12241
|View full text |Cite
|
Sign up to set email alerts
|

Viperin is an iron-sulfur protein that inhibits genome synthesis of tick-borne encephalitis virus via radical SAM domain activity

Abstract: SummaryViperin is an interferon-induced protein with a broad antiviral activity. This evolutionary conserved protein contains a radical S-adenosyl-Lmethionine (SAM) domain which has been shown in vitro to hold a [4Fe-4S] cluster. We identified tick-borne encephalitis virus (TBEV) as a novel target for which human viperin inhibits production of the viral genome RNA. Wt viperin was found to require ER localization for full antiviral activity and to interact with the cytosolic Fe/S protein assembly factor CIAO1. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
145
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(148 citation statements)
references
References 51 publications
1
145
1
Order By: Relevance
“…In contrast to our results with FPPS, it was shown that, whereas localization of viperin to the ER was essential to reduce the titer of TBEV, this was not dependent on identity of the ER-localizing sequence (24). Significantly, mutation of the conserved cysteine residues or the C-terminal tryptophan of viperin, which is important for installation of the [Fe 4 S 4 ] cluster by CIAO1, abolished viperin inhibition of TBEV replication, indicating that an intact [Fe 4 S 4 ] cluster was essential for activity.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to our results with FPPS, it was shown that, whereas localization of viperin to the ER was essential to reduce the titer of TBEV, this was not dependent on identity of the ER-localizing sequence (24). Significantly, mutation of the conserved cysteine residues or the C-terminal tryptophan of viperin, which is important for installation of the [Fe 4 S 4 ] cluster by CIAO1, abolished viperin inhibition of TBEV replication, indicating that an intact [Fe 4 S 4 ] cluster was essential for activity.…”
Section: Discussioncontrasting
confidence: 99%
“…Unlike viruses such as influenza A that bud from cholesterol-rich lipid rafts and are thus sensitive to FPPS inhibition, flaviviruses such as TBEV do not require lipid rafts for budding. Indeed it has been shown that inhibition of FPPS by ibandronate has no effect TBEV replication (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early studies showed that viperin is induced in various cell types by IFN-α and IFN-β, associates with the cytosolic face of the endoplasmic reticulum (ER), and inhibits human cytomegalovirus replication when preexpressed in human fibroblasts (8). Since then, viperin has been shown to be induced by several factors, including lipopolysaccharide (10)(11)(12), and to inhibit a broad range of viruses, including HIV-1 (13), West Nile virus (14), hepatitis C virus (15,16), dengue virus type 2 (17), influenza A virus (18), and tick-borne encephalitis virus (19). Gene-profiling microarray studies have shown that the viperin gene is one of the most highly inducible ISGs upon infection with a wide range of RNA viruses (20).…”
mentioning
confidence: 99%
“…The chemical versatility of these clusters is utilized in fundamental life processes such as energy production, metabolic conversions, DNA maintenance, gene expression regulation, protein translation, and the antiviral response ( Fig. 1) (2)(3)(4). In eukaryotes, Fe/S proteins are found in or associated with the mitochondrion, endoplasmic reticulum, cytosol, and the nucleus.…”
Section: Ubiquitous Iron-sulfur Clusters and Their Synthesis: An Overmentioning
confidence: 99%